2014
DOI: 10.1097/meg.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk factors associated with the development of fundic gland polyps

Abstract: Age and the long-term use of PPIs were risk factors for the presence of FGPs; the long-term use of PPIs was a particularly strong risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
(50 reference statements)
3
24
1
2
Order By: Relevance
“…In the present study, hyperplastic polyps made up 69.3% of all the reported gastric polyps, which agrees with the results obtained by Markowski AR et al, who reported that, although most gastric polyps in the US are of the fundus type, 25% to 71% of the polyps found in their study were hyperplastic [9]. The incidence of hyperplastic polyps increases with age and they are mostly observed in people over 65 [1,4]. These findings are consistent with the present findings regarding the higher prevalence of polyps in the age group over 60 and the highest frequency of polyp type pertaining to hyperplastic polyps.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the present study, hyperplastic polyps made up 69.3% of all the reported gastric polyps, which agrees with the results obtained by Markowski AR et al, who reported that, although most gastric polyps in the US are of the fundus type, 25% to 71% of the polyps found in their study were hyperplastic [9]. The incidence of hyperplastic polyps increases with age and they are mostly observed in people over 65 [1,4]. These findings are consistent with the present findings regarding the higher prevalence of polyps in the age group over 60 and the highest frequency of polyp type pertaining to hyperplastic polyps.…”
Section: Discussionsupporting
confidence: 82%
“…H. pylori infection was three times more prevalent in women than in men, although no significant relationships were observed between gender and the type of polyp. A review of literature shows that, hyperplastic polyps were the most common type of polyp concomitant with H. pylori infection [3,4,6] In line with other studies, most polyps had no concomitant pathologies in the present study. In a study conducted by Markowski AR et al on the clinical symptoms of polyps, most polyps were found to be asymptomatic and were detected incidentally, also in the present study, the most frequent clinical symptom reported was abdominal pain [9].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Recently, it was noticed that Fundic Gland Polyps (FGP's) are more frequently seen. There are reports in the literature stating that this condition is associated with the long-term use of Proton Pump Inhibition (PPI) [2].…”
mentioning
confidence: 99%